Serum CA125 in combination with ferritin improves diagnostic accuracy for epithelial ovarian cancer. Issue 2 (3rd April 2018) - Zhao, J; Guo, N; Zhang, L; Wang, L
Abstract: Introduction: CA125 has poor sensitivity and low specificity for detecting early ovarian cancer. Serum ferritin is elevated in many malignancies. We evaluated the performance of ferritin alone and in combination with CA125 as a diagnostic tool to detect epithelial ovarian cancer (EOC). Methods : CA125 and ferritin were detected in the serum of 50 healthy control (HC), 50 women with benign gynaecological conditions and 124 women with EOC. The relationship between serum ferritin and CA125 and each of the clinicopathological parameters was assessed, and their diagnostic accuracy for discriminating ovarian cancer determined. Results : Serum ferritin and CA125 were higher in patients with EOC compared to HCs and patients with benign conditions (both p < 0.001). There was no relationship between levels of ferritin and CA125. Both ferritin and CA125 discriminated HC from EOC ( p < 0.05), but ferritin showed better diagnostic accuracy than CA125 ( p = 0.048). Ferritin was superior to CA125 in discrimination early EOC ( p = 0.002), but in advanced stages, CA125 was superior ( p = 0.026). A combination of ferritin and CA125 marginally increases the diagnostic accuracy to discriminate EOC from HCs. Conclusion : Ferritin discriminates between HCs and EOC patients, especially in early stage disease. The combination of serum ferritin and CA125 provides the higher diagnostic accuracy to screen for EOC. Serum ferritin could serve as an EOC biomarker to complement the standard CA125 test.